Discovery of potent macrocyclic HCV NS5A inhibitors. Issue 15 (1st August 2016) - Yu, Wensheng; Vibulbhan, Bancha; Rosenblum, Stuart B.; Martin, Gregory S.; Vellekoop, A. Samuel; Holst, Christian L.; Coburn, Craig A.; Wong, Michael; Selyutin, Oleg; Ji, Tao; Zhong, Bin; Hu, Bin; et al.
Graphical abstract: Abstract: HCV NS5A inhibitors have demonstrated impressive in vitro virologic profiles in HCV replicon assays and robust HCV RNA titer reduction in the clinic making them attractive components for inclusion in an all oral fixed-dose combination (FDC) regimen for the treatment of HCV infection. Merck's effort in this area identified MK-4882 and MK-8325 as early development leads. Herein, we describe the discovery of potent macrocyclic NS5A inhibitors bearing the MK-8325 or MK-4882 core structure.